(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
Judicial impartiality is one of the most important issues for the democratic civil process, which has undergone numerous conceptual reformulations, adapting itself over time and the configurations of the state and jurisdiction. However, impartiality can sometimes be affected by external circumstances that are not even known by the subjects, but which exert cognitive influences in the formation of the interpreters understanding. In this sense, cognitive biases are an example of this, altering perception and interpretation. In the judicial sphere, cognitive biases affect judges and their effects can manifest themselves differently in each case, depending, for example, on the nature of the subjects in litigation. Given this context, this paper seeks to answer the following: to what extent can judicial impartiality be affected by cognitive biases in cases involving repeat players? Considering this problem, the main objective of the study is to investigate the cognitive biases applied to the jurisdiction, especially the one involving repeat players. In methodological terms, the work adopts the phenomenology-hermeneutics, the method of monographic procedure and the technique of bibliographic research. In the end, it is concluded that impartiality can be affected to a large extent by cognitive biases in processes involving habitual players, both to their benefit and to their detriment. In fact, biases operate in all processes, but in cases of this nature they can be leveraged. And with that, impartiality is broken for "the good" and "the bad" of the players, which must be avoided in respect of this constitutional guarantee.